Isolation and characterization of antithrombin peptides from the saliva of Malaysian leeches - Alaama, Mohammed; Helaluddin, Abul Bashar Mohammed; Mohammad Ghawi, Abbas; Merzouk, Ahmed; Abdualkader, Abdualrahman Mohammed; Awang, Mohamed (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2014)
Purpose: To isolate and characterize the antithrombin compounds of Malaysian leeches’ saliva collection (LSC) for use as anticoagulant proteins and peptides. Method: Reversed phase - high performance liquid chromatography (RP-HPLC) was used to isolate all proteins from LSC. All isolated proteins were tested for anticoagulant activity by applying two tests, thrombin time test and the inhibition of the amidolytic activity of thrombin on the chromogenic substrate (S-2238). The molecular weights of isolated active compounds were identified using tricine sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS- PAGE). Results: More than 40 proteins were isolated from LSC using RP-HPLC. Two compounds (protein 1 and protein 2) were found to be active as they increased thrombin time by 30.26 and 36.75%, respectively and inhibited the amidolytic activity of thrombin. as evaluated by measuring the conversion of the chromogenic substrate (S-2238). Decrease in the conversion of the substrate (S-2238) by 31.10 and 41.61%, respectively was observed. The molecular weights of the proteins (6.289 and 14.255 kDa, respectively) had no similarity with other leech species. Conclusion: Two antithrombin proteins with anticoagulant properties were isolated from the saliva of Malaysian leeches using one-step isolation procedure. The proteins did not show any similarity to previous isolated proteins from leech.